THE PROJECTION OF CULTURAL SHIFT REJUVINATION ABOUT FOSTERING ISLAMIC EDUCATION AND ITS COUNTERPART WITHIN MALAY COMMUNITY - Nurmawati, Nurmawati; Zulfitri, Zulfitri; Afna, Mauloeddin; Amri, Khairul (Jurnal Ilmiah Peuradeun, 2020)
The article projected the cultural identity resistance to preserve the young generations within the Malay community among Southeast Asia nations. The article uncovered the challenge of cultural shifts young people to bear with global life. The Modernism way of life might not suit to the original way of life; it only took to hedonism, personal logic, and contemporary then merely to maturity. At the same time, it might also endanger the existence of Malay Identity for the long term. This article conveyed the friction of cultural shift among Malay young people who influenced to expose the change in their personal identity and role model. The friction carried a serious threat to the whole Malay as an origin identity. The article composed the research focuses on the Malay race tradition who embraces Islam as a way of life. The Malay community embraces Islamic Identity as a cultural feature ?adat bersendikan syarak? the collocational Islamic tradition within the cultural identity. The identity-preserved religion and culture inseparable and integrated one to another as ethnographically proposed research articles applied implemented participant and key informant interviewing from issues phenomenon.